2010
DOI: 10.1038/jhh.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

Association between vascular endothelial growth factor and hypertension in children and adolescents type I diabetes mellitus

Abstract: The aim of the study was to analyse the relationship between the serum level of vascular endothelial growth factor (VEGF) and the incidence of hypertension (HT) in children and adolescents with type I diabetes mellitus (T1DM). One hundred and five patients with T1DM were enrolled in the study. The control group consisted of 30 healthy controls. All the T1DM patients were subjected to biochemical analyses, ophthalmologic examination and 24-h blood pressure monitoring. Besides, all the patients and healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
1
21
0
3
Order By: Relevance
“…Furthermore, many diabetic complications interfere with VEGF systemic values, which may cause confusion in interpretation of plasma VEGF as a marker of only DR [20][21][22], so the absence of diabetic patients without complications or healthy control group for comparison could be another limitation of this study.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, many diabetic complications interfere with VEGF systemic values, which may cause confusion in interpretation of plasma VEGF as a marker of only DR [20][21][22], so the absence of diabetic patients without complications or healthy control group for comparison could be another limitation of this study.…”
Section: Discussionmentioning
confidence: 89%
“…Our previous studies and studies by other authors have shown that long-term diabetic complications occur after 5 years of the disease [1, 4, 8]. Therefore for the purpose of analyses the study patients with T1DM were divided into two subgroups: patients with duration of diabetes ≤5 years and those with disease duration >5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic control of diabetes mellitus is one of the most important factors, but not the only one, that affects the risk of long-term angiopathic complications [4–7]. Several proofs of evidence indicates that the risk of long-term diabetic complications is increased when hyperglycaemia is accompanied by lipid metabolism disorders and high blood pressure values [3, 6, 8]. In our previous studies we showed a correlation between systolic blood pressure values and serum levels of vascular endothelial growth factor (VEGF) in children and adolescents with type 1 diabetes mellitus (T1DM) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided some epidemiological and pathophysiological insights. [26][27][28] Further work is clearly needed.…”
mentioning
confidence: 99%